Determinan Keputusan Perempuan Menikah untuk Bekerja di Provinsi Sumatera Barat - Wina Yulita; Anis, Ali (Universitas Negeri Padang, 2024)
Being a working mother or a non-working housewife is a factor that can influence the choice of married women in determining the best attitude in the household. This study aims to determine the factors that influence the decision of married women to work or not work in West Sumatra Province. The data was obtained from the National Labor Force Survey in 2022. The results and analysis show that the level of education, age, number of household members, training/courses have a significant positive effect, while the husband's income, the presence of toddlers, the region of residence, and work experience have a negative and significant effect on the work participation of married women in West Sumatra in 2022. Policy recommendations from the research results for the government and the community to increase awareness about the importance of education and training for women in West Sumatra Province to improve their abilities and employment opportunities.